Can Self-Tracking Solutions Help with Understanding Quality of Smart, Connected Products? - Schiller, Barbara; Brogt, Tobias; Schuler, J. Peter M.; Strobel, Gero (Proceedings of the 26th European Conference on Information Systems (ECIS), 2018)
Smart connected products (SCPs) have gained significant attention in different domains because they offer numerous benefits and change the way of competition and value creation. While quality is im-portant for SCPs, no holistic quality model is available to target the present quality problems. Further-more, since the concept of an SCP is quite abstract, a bottom-up approach that starts with a concrete example seems suitable. Therefore, this paper identifies the five key components of SCPs and maps them to self-tracking solutions (STS) in order to show that STSs are suitable substitutes. We also analyse quality models in corresponding areas to verify the absence of a holistic quality model for the selected example. This contribution identifies the research gap regarding holistic, stakeholder-oriented quality models and helps researchers understand SCPs better.
Keywords: Quality; Smart Connected Product; Self-Tracking; Internet of Things